Effect of new solid and liquid fertilizers on the production of coffee (Coffea arabica) seedlings under nursery cultivation in Chirinos, Cajamarca, Peru - Jaulis C., Juan Carlos (2020)
The obtaining of vigorous plants in nursery guarantees the successful development of crops in the field. Fertilization of plants in nursery is one of the fundamental pillars in the establishment of crops that can remain for more than 15 years in the field. In this regard, the objective of this study was to determine the effect of organic fertilizers Churufer and Churubiol made in Finca Churupampas Chirinos-Cajamarca-Peru for the production of coffee seedlings (Yellow Caturra variety) from nursery. The experiment was conducted as a Randomized Complete Block Design (RCBD) with sixteen treatments, three blocks and ten plants per experimental unit. The organic fertilizers used were T1) Control without organic fertilizer, T2) Churufer (biosol), T3) Pachacushi (compost), T4) Guano Island, T5) Churubiol (biol), T6) Kapsitron (biol), T7) Huallquin-fer (biol), T8) Churufer+Churubiol, T9) Churufer+Kapsitron, T10) Churufer+Huallquin-fer, T11) Pachacushi+Churubiol, T12) Pachacushi+Kapsitron, T13) Pachacushi+Huallquin[1]fer, T14) Guano Island+Churubiol, T15) Guano Island+Kapsitron, T16) Guano Island +Huallquin-fer. After 120 days, it was verified that coffee seedlings treated with the combination of organic fertilizers Churufer+Churubiol presented the best results in Plant Height (15,64 cm), Number of Leaves (8,83), Stem Diameter (2,62 mm), Fresh Weight of Leaves (3,09 g), Fresh Weight of Stem (0,0054 g), Fresh Weight of Root (0,0100 g) and Total Fresh Weight (3,0988 g). In this way, it is concluded that the organic fertilizers elaborated in Finca Churupampas significantly improved the size and weight of coffee seedlings.